2019
DOI: 10.1097/pcc.0000000000001938
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Rater Reliability Between Critical Care Nurses Performing a Pediatric Modification to the Glasgow Coma Scale*

Abstract: Objectives: Estimate the inter-rater reliability of critical care nurses performing a pediatric modification of the Glasgow Coma Scale in a contemporary PICU. Design: Prospective observation study. Setting: Large academic PICU. Patients/Subjects: All 274 nurses with permanent assignments in the PICU were eligible to participate. A subset of 18 nurses were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The GCS is a cursory measurement tool with low interrater reliability that was not developed to detect subtleties in encephalopathy and may not be an appropriate tool to identify neurologic failure in children with ACLF. [ 16 ] Furthermore, there are no studies that compare how GCS and hepatic encephalopathy grades correlate in children with liver failure. An additional critique of the status 1B criteria for ACLF is that cardiovascular compromise is not included in the criteria despite high vasopressor requirements being demonstrated in ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…The GCS is a cursory measurement tool with low interrater reliability that was not developed to detect subtleties in encephalopathy and may not be an appropriate tool to identify neurologic failure in children with ACLF. [ 16 ] Furthermore, there are no studies that compare how GCS and hepatic encephalopathy grades correlate in children with liver failure. An additional critique of the status 1B criteria for ACLF is that cardiovascular compromise is not included in the criteria despite high vasopressor requirements being demonstrated in ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted on patients aged 1 month to 17 years who were admitted to our tertiary PICU between March 2015 and November 2019. The modified GCS scoring system was used [3]. The GCS of patients and its relationship with prognosis and etiology were assessed by dividing the study population into three groups depending on the level of consciousness at admission: the first group was comprised of those with a GCS score of 10-12 (mild encephalopathy), the second group had moderate encephalopathy (GCS: 7-9), and the third group had severe encephalopathy (GCS: [14,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…It is a very serious condition that necessitates immediate medical decision making upon arrival at the pediatric emergency department or pediatric intensive care unit (PICU) [1]. The most common scoring system used for assessment of consciousness is the Glasgow coma scale (GCS), and a modified version of the GCS is used in pediatric patients [2,3]. Pediatric coma is generally defined as having a GCS of < 12 for at least 6 hours [4].…”
Section: Introductionmentioning
confidence: 99%
“…The individual components are also listed, along with the total score (e.g., E3V3M5, GCS 11). Studies have shown that the pediatric scores have excellent inter-rater reliability 22 (►Table 1).…”
Section: Assessment Of Concussionmentioning
confidence: 99%